FPGA Implementation of IEC-61131-3-Based Hardware Aided Counters for PLC - Miroslaw Chmiel; Robert Czerwinski; Andrzej Malcher (Applied Sciences, 2021)
The article discusses counters defined in the IEC 61131-3 standard. The possible implementations of standard counters function blocks in FPGAs are presented. First, counters are implemented as classical hardware-based modules. Second, counters are designed as the FPGA built-in memory blocks with a single common executing unit. These solutions are compared to each other and compared with counters realized in commercially available PLCs like Siemens SIMATIC S7 controllers. The structure of integrated hardware–software CPU with counters is presented. The paper presents how the designer can take advantage of the specific features of the FPGA devices to optimize both the utilization of resources and speed of realization of the particular blocks. Experimental results prove the high efficiency of the proposed solutions.